Characterizations of GaN, blue and green LEDs. - Huynh, Nguyen. (2009)
The purpose of this report is to provide the overview of the internship at Institute of Materials Research and Engineering. This report reports the research results on the designated topic – Characterizations of GaN, blue and green LEDs – as well as the working experiences that I as an intern student have been able to learn after 10 weeks of Industrial Internship at IMRE.